PENYULUHAN TENTANG EDUKASI IBU DALAM MENGATASI PICKY EATER PADA ANAK BALITA - Dewi, Ratna; Oktavia, Sesmi Nanda; Larasati, Timmy; Dielsa, Maya Fernanda; Azhari, Armita Sri; Febriani, Leni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This Community Service Activity was carried out in the form of counseling about maternal education in dealing with picky eaters in children in Jorong Tanjung Sari Kampung Dua Koto Baru Mahakarya District. West Pasaman. Partners in this community service activity are cadres and village midwives in Jorong Tanjung Sari Kampung Dua with the target being mothers who have children under five. The location for this activity was chosen because there are many nutritional problems in toddlers. One of the most striking problems related to picky eaters in toddlers is significant weight loss, or the child's weight being below the normal limit or the yellow line on the card. healthy (KMS). Therefore, it is necessary to carry out community service activities, especially mothers who have children under five. The solution carried out in this community service activity is in the form of providing educational counseling to mothers in dealing with picky eaters in toddlers. The purpose of this community service activity is to increase mothers' knowledge in dealing with picky eaters. The benefit of this activity is so that parents, especially those who have children under five, know how important it is to deal with picky eaters to prevent nutritional problems in children under five so that children under five grow well develop healthily.Keywords: Picky Eater, Mother, and Toddler